The Haemophilus influenzae Type b hcsA and hcsB Gene Products Facilitate Transport of Capsular Polysaccharide across the Outer Membrane and Are Essential for Virulence - Sukupolvi-Petty, Soila (American Society for Microbiology, 2006)
Haemophilus influenzae type b is a common cause of invasive bacterial disease, especially among children in underdeveloped countries. The type b polysaccharide capsule is a polymer of ribose and ribitol-5-phosphate and is a critical determinant of virulence. Expression of the type b capsule is dependent upon the cap b locus, which consists of three functionally distinct regions, designated regions 1 to 3. Region 3 contains the hcsA and hcsB genes, which share significant homology with genes that have been implicated in encapsulation in other pathogenic bacteria but have unclear functions. In this study, we inactivated hcsA alone, hcsB alone, and both hcsA and hcsB together and examined the effects of these mutations on polysaccharide transport and bacterial virulence properties. Inactivation of hcsA alone resulted in accumulation of polysaccharide in the periplasm and a partial decrease in surface-associated polysaccharide, whereas inactivation of hcsB alone or of both hcsA and hcsB together resulted in accumulation of polysaccharide in the periplasm and complete loss of surface-associated polysaccharide. All mutations eliminated serum resistance and abrogated bacteremia and mortality in neonatal rats. These results indicate that the hcsA and hcsB gene products have complementary functions involved in the transport of polysaccharide across the outer membrane and are essential for virulence.